Don't worry, you just have to get used to these problems! You can do it girl!!
So, it doesn't matter where you start. I would start finding the x in the first equation, like this:
x - 2y = 5
x = 5 - 2y
Which is really easy, isn't it?
Now you know that x is equal to 5 - 2y, so you can substitute the x in the second equation. (You could have done the same solving by y, it doesn't matter :D )
3 ( 5 - 2y ) - 5y = 8
15 - 6y - 5y = 8
- 6y - 5y = 8 - 15
-11y = -7
y = -7/-11 = 7/11
Now you found your y! Let's substitute it in the first equation. (The beginner one, not the one that you worked on)
x - 2 (7/11) = 5
x - 14/11 = 5
x = 5 + 14/11
x = 69/11
I know you got it now! ;) Otherwise ask me whatever you want!